2002
DOI: 10.1097/00005392-200209000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Microdissection Testicular Sperm Extraction for Nonobstructive Azoospermia

Abstract: In nonobstructive cases, especially those of the Sertoli-cell-only syndrome, microdissection TESE can effectively retrieve spermatozoa and minimize the risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 18 publications
3
86
0
2
Order By: Relevance
“…Patients diagnosed with hypospermatogenesis by histological examination should have obtainable testicular sperm. 40 35 They also reported that SRRs by microdissection TESE for maturation arrest and SCO were 75% and 33.9%, respectively, whereas those by conventional TESE were 37.5%, and 6.3%. 35 Recently, Ramasamy et al reported the outcomes of 460 patients with NOA treated with microdissection TESE.…”
Section: Sperm Retrieval Rate By Microdissection Tesementioning
confidence: 98%
See 4 more Smart Citations
“…Patients diagnosed with hypospermatogenesis by histological examination should have obtainable testicular sperm. 40 35 They also reported that SRRs by microdissection TESE for maturation arrest and SCO were 75% and 33.9%, respectively, whereas those by conventional TESE were 37.5%, and 6.3%. 35 Recently, Ramasamy et al reported the outcomes of 460 patients with NOA treated with microdissection TESE.…”
Section: Sperm Retrieval Rate By Microdissection Tesementioning
confidence: 98%
“…40 35 They also reported that SRRs by microdissection TESE for maturation arrest and SCO were 75% and 33.9%, respectively, whereas those by conventional TESE were 37.5%, and 6.3%. 35 Recently, Ramasamy et al reported the outcomes of 460 patients with NOA treated with microdissection TESE. 36 In that report, the SRR by microdissection TESE was 57%, whereas that by conventional TESE was 32%.…”
Section: Sperm Retrieval Rate By Microdissection Tesementioning
confidence: 98%
See 3 more Smart Citations